Mixing Power Requirement Determination in Agitated Drum Using Dimensional Analysis - Horváth, Dániel; Poós, Tibor (International Journal of Engineering and Management Sciences, 2023)
The mixing of granular materials in an agitated drum can be characterized by the dimensionless power equation. The equation was created by dimensional analysis, for which the parameters affecting the mixing power requirement were collected based on the literature. The most important of these are the rotational speed, the drum loading factor, the geometric and physical properties of the mixing drum and the granular materials.  The dimensionless power equation is used to estimate with reasonable accuracy the Power number within the given range of applicability , which has been validated by measurements. From the Power number, the mixing power requirement of the mixed granular material can be calculated, which can be used as operational data for selecting the mixing motor.